Bio-Wrap Cumin: Intelligent Edible film Berbasis Kitosan Dengan Penambahan Ekstrak Kunyit Sebagai Antimikroba Dan Indikator Kerusakan Daging: Bio-Wrap Cumin: Intelligent Edible film Berbasis Kitosan Dengan Penambahan Ekstrak Kunyit Sebagai Antimikroba Dan Indikator Kerusakan Daging - Nursari, Elisa Tri (Universitas Duta Bangsa Surakarta, 2024)
Meat is one of the sources of protein that is widely consumed by the public. Meat is easily damaged both physically, chemically and microbiologically. The damage that occurs is generally due to microbial activity. One of the damages to meat is indicated by changes in pH. Meat that has a higher pH indicates the beginning of meat damage. In order to determine the level of meat damage, an indicator of meat color change is needed. One thing that can be done is to use primary packaging from chitosan with the addition of turmeric extract as an antimicrobial (intelligent edible film). Changes in pH are seen in intelligent edible film which in alkaline conditions will become brownish or red and in acidic conditions will become bright yellow. The results of this literature study aim to provide an alternative meat packaging that acts as an indicator of meat damage, is environmentally friendly and safe to consume. The method used in this literature study is a narrative method that reviews literature and analyzes microbial inhibition zones and characterization of intelligent edible films such as tensile and elongation tests produced. The inhibition zone in Staphylocaccus aureus bacteria was 8.63 mm at 40% curcumin concentration, Escherichia coli 19.88 mm and Shigella dysenteriae 15.5 mm at 100% turmeric extract, intelligent edible film can be an alternative to maintain the quality of meat products.